Radiosynovectomy of Painful Synovitis of Knee Joints Due to Rheumatoid Arthritis by Intra-Articular Administration of 177 Lu-Labeled Hydroxyapatite Particulates: First Human Study and Initial Indian Experience - Ajit Shinto; K Kamaleshwaran; Sudipta Chakraborty; K Vyshakh; S Thirumalaisamy; S Karthik; V Nagaprabhu; K Vimalnath; Tapas Das; Sharmila Banerjee (World Journal of Nuclear Medicine)
The aim of this study is to assess the effectiveness of Radiosynovectomy (RSV) using 177 Lu-labeled hydroxyapatite ( 177 Lu-HA) in the treatment of painful synovitis and recurrent joint effusion of knee joints in rheumatoid arthritis (RA). Ten patients, diagnosed with RA and suffering from chronic painful resistant synovitis of the knee joints were referred for RSV. The joints were treated with 333 ± 46 MBq of 177 Lu-HA particles administered intra-articularly. Monitoring of activity distribution was performed by static imaging of knee joint and whole-body gamma imaging. The patients were evaluated clinically before RSV and at 6 months after the treatment by considering the pain improvement from baseline values in terms of a 100-point visual analog scale (VAS), the improvement of knee flexibility and the pain remission during the night. RSV response was classified as poor (VAS < 25), fair (VAS ≥ 25-50), good (VAS ≥ 50-75) and excellent (VAS ≥ 75), with excellent and good results considered to be success, while fair and poor as failure and also by range of motion. Three phase bone scan (BS) was repeated after 6 months and changes in the second phase of BS3 were assessed visually, using a four-degree scale and in the third phase, semiquantitatively with J/B ratio to see the response. Biochemical analysis of C-reactive protein (CRP) and fibrinogen was repeated after 48 h, 4 and 24 weeks. In all 10 patients, no leakage of administered activity to nontarget organs was visible in the whole-body scan. Static scans of the joint at 1 month revealed complete retention of 177 Lu-HA in the joints. All patients showed decreased joint swelling and pains, resulting in increased joint motion after 6 months. The percentage of VAS improvement from baseline values was 79.5 ± 20.0% 6 months after RS and found to be significantly related to patients′ age (P = 0.01) and duration of the disease (P = 0.03). Knees with Steinbrocker′s Grades 0 and I responded better than those with more advanced changes (Steinbrocker′s Grades III and IV) in terms of VAS improvement (75% vs. 45.8%) (P < 0.001). The overall success rate (VAS ≥ 50) was 80%. Remission of pain during the night was achieved in 100%, and knee flexibility was improved in 80%. The changes in the blood pool phase before RSV were 3.2 ± 0.7 and after the therapy 1.4 ± 0.7 (P < 0.001). The J/B ratio was: Before RSV 2.4 ± 0.3; after treatment 1.0 ± 0.2 (P < 0.05). CRP concentration 4 and 24 weeks after the therapy was significantly lower than before treatment. The fibrinogen level was not different before and after RSV. RSV side-effects assessed for the whole follow-up period were minor and not significant. RSV with 177 Lu-HA was safe and effective in patients with knee joint chronic painful synovitis of rheumatoid origin. It exhibited significant therapeutic effect after 6 months follow-up period with no significant side-effects. The preliminary investigations reveal that 177 Lu-labeled HA particles hold considerable promise as a cost-effective agent for RSV. More elaborate and controlled clinical trials are necessary to evaluate the therapeutic efficacy and safety of the agent compared with the treatment with other radionuclides and glucocorticosteroids.